JUSTIFICATION OF THE PRINCIPLES OF MOBILE AVIATION TRANSPORT SYSTEMS FORMATION - Олег, М. (Science-based technologies, 2012)
The main development problems of world transport system are observed, prospects of its development and feature. of basic new type of transport systems — mobile aviation transport systems are analyzed. Conditions in which creation of such systems and the list of the main activities which are necessary for executing at their designing expedient are proved.